MÖNCH detector enables fast and low‐dose free‐propagation phase‐contrast computed tomography of in situ mouse lungs. (6th February 2018) - Dullin, Christian; Albers, Jonas; Tromba, Giuliana; Andrä, Marie; Ramilli, Marco; Bergamaschi, Anna
Abstract : The high detective quantum efficiency of the novel charge‐integrating hybrid detector MÖNCH enables in situ mouse lung imaging at a pixel size of 25 µm in 10 s with an entrance dose lower than 70 mGy, thereby enabling longitudinal in vivo synchrotron free‐propagation phase‐contrast computed tomography lung studies in mice. Abstract : Due to the complexity of the underlying pathomechanism, in vivo mouse lung‐disease models continue to be of great importance in preclinical respiratory research. Longitudinal studies following the cause of a disease or evaluating treatment efficacy are of particular interest but challenging due to the small size of the mouse lung and the fast breathing rate. Synchrotron‐based in‐line phase‐contrast computed tomography imaging has been successfully applied in lung research in various applications, but mostly at dose levels that forbid longitudinal in vivo studies. Here, the novel charge‐integrating hybrid detector MÖNCH is presented, which enables imaging of mouse lungs at a pixel size of 25 µm, in less than 10 s and with an entrance dose of about 70 mGy, which therefore will allow longitudinal lung disease studies to be performed in mouse models.